2012
DOI: 10.4236/jbise.2012.55036
|View full text |Cite
|
Sign up to set email alerts
|

Arterial pulsation on a human patient simulator improved students’ pulse assessment

Abstract: Even with basic cardiovascular lectures, undergraduates do not usually experience the reality of palpation and, therefore, cannot integrate their physiological knowledge. We created a pulse training scenario of human patient simulators (HPS) to recognize and assess the normal and arrhythmic pulse of the radial artery. All 25 participants were recruited as volunteers to the study from the School of Allied Health Sciences, Kitasato University. Participants received training in radial palpation of arrhythmias on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Its controlling software relies on highly structured information that establishes, for example, the heart rate and blood pressure of the manikin. The behavior and health condition of this manikin can pass through several states as part of a simulation scenario [13]. It is a graph where each node is a state of the manikin -i.e., a configuration of the simulator -and the transformations according to students' actions, e.g., one applies medication to the manikin to reduce the heart rate [14].…”
Section: Foundations and Related Workmentioning
confidence: 99%
“…Its controlling software relies on highly structured information that establishes, for example, the heart rate and blood pressure of the manikin. The behavior and health condition of this manikin can pass through several states as part of a simulation scenario [13]. It is a graph where each node is a state of the manikin -i.e., a configuration of the simulator -and the transformations according to students' actions, e.g., one applies medication to the manikin to reduce the heart rate [14].…”
Section: Foundations and Related Workmentioning
confidence: 99%
“…One of the earliest commercially available simulators used for medical training was the Harvey ® (Laerdal, Stavanger, Norway), a mannequin that simulates several cardiopulmonary functions, including arterial pulse. This system is still used and has been shown, from very early on, to provide good results [ 27 , 28 , 29 ]. One other relevant commercial device is the Self-Teaching System (STS) for Cardiac Auscultation (Cardionics, Webster, TX, USA), that allows training of palpation and auscultation, even though no studies were found to confirm its effectiveness.…”
Section: Introductionmentioning
confidence: 99%